Public sector performance, corruption and state capture in a globalized world - Rose-Ackerman, Susan (Routledge, 2024)
"This collection examines the difficult task of reforming governments worldwide to meet citizens' needs and aspirations. It advances constructive efforts to enhance public accountability while recognizing the complex ways in which corruption, greed, and state capture undermine the legitimacy and performance of government. The contributors are political scientists, lawyers, and economists who bring a cross-disciplinary approach to their chosen subjects. The first group of chapters deals with public sector performance, development, and public participation. Complementary pieces by a practitioner and a scholar confront the challenges of achieving reform in countries with difficult political environments and extensive poverty and inequality. The second group emphasizes the way corruption and state capture limit the accountability and effectiveness of governments in both developing and wealthy countries. The contributions consider the institutional roots of dysfunctional government and their links to the private sector. Taken together, the volume surveys a wide range of topics with theoretical arguments and empirical findings that provide insights into real-world problems and policymaking dilemmas. Inspired by Susan Rose-Ackerman's fifty-year exploration of public policymaking, public law, and corruption, the collection will be an invaluable resource for researchers, academics and policy makers working in the areas of Public law, Anticorruption, and Political-Economy"-- Provided by publisher.
Keywords: Government productivity.; Public administration.; Political corruption.; State governments.; Organizational change.; Organizational effectiveness.; elektronické knihy; electronic books